Factors Related TO Waste Disposal Behavior AMONG Students AT Jelambar 03 Pagi Public Elementary School West Jakarta - Fuza Manis Segara; Rismawati Pangestika (Journal Hygeia Public Health, 2026)
Introduction: Waste disposal behavior is an important aspect in maintaining environmental cleanliness and public health. Waste that is not handled properly will cause various environmental problems. The purpose of this study was to determine the factors related to waste disposal behavior among students of SDN Jelambar 03 Pagi West Jakarta. Method: This type of research is quantitative with a Cross Sectional design. The population in this study were all grades IV and V, totaling 110 students. The analysis conducted was univariate and bivariate analysis. Results and Discussion: Univariate results showed good waste disposal behavior (73.6%), high knowledge (51.8%), positive attitudes (50.9%), availability of adequate facilities (51.8%), and supportive teacher support (56.4%). Bivariate results show a significant relationship between the variables of knowledge (p-value = 0.017), attitude (p-value = 0.000), and teacher support (p-value = 0.003) with students' waste disposal behavior, there is no relationship between the availability of facilities and waste disposal behavior (p-value = 0.817). Conclusion: It is recommended that schools can increase student involvement in maintaining environmental cleanliness by utilizing waste and creating educational media.